Perancangan, Pembuatan dan Pengujian Omnidirectional Vehicle - Muljowidodo Muljowidodo; Cahyadi Setiawan (Mesin, 2004)
Research and development of Robot Vision activity requirs a Moving platform with high mobility on translation as well as rotation movement. Omnidirectional vehicle reported here has optimum planar movement in the form translational movement on any direction as well as turning radius from zero to infinity, therefore it is suitable as a moving platform for research activities on 2 dimensional Robot Vision. Testing and measurement on the accuracy of vehicle straight trajectory on different direction have been carried out. Some error compensation algorithm has been applied and some good results on reducing trajectory errors have been observed.